Agroecological transitions reveal trade-offs and synergies among ecosystem services - Mathieu Delandmeter; Bruno Basso; Jérôme Bindelle; Benjamin Dumont (Science of The Total Environment, 2026)

Livestock Integration Into Cropping Systems Enhances Their Climate Change Resistance and Mitigation While Reducing Their Environmental Impacts - Mathieu Delandmeter; Bruno Basso; Xavier Fettweis; Christophe Lacroix; Pierre Aubry; Jérôme Bindelle; Benjamin Dumont (Global Change Biology, 2026)
The sustainability of cropping systems is linked to their circularity, which is their ability to close resource cycles such as carbon and nitrogen through strategies for managing crop residues, byproducts, and other inputs. Here, we investigate three crop rotations—business‐as‐usual (BAU), vegan, and integrated crop‐livestock systems (ICLS)—varying in livestock integration, crop residue fate, and human diet sustained. Under ten climate change scenarios, we compare their impacts on multiple ecosystem services during 24 years over 541,800 ha in Belgium using a validated crop model. All three circularity scenarios are found to be net greenhouse gas (GHG) emitters, with increasing intensity under climate change. The BAU system, favoring cash crops such as sugarbeet or potato, demonstrates the highest productivity, which, however, is highly variable across years and comes with greater environmental impacts such as GHG emissions (+45% and +23% compared to ICLS and Vegan in average—i.e., across all sites and climate scenarios). The Vegan system has lower carbon sequestration than the ICLS due to the lack of pasture and livestock, which, however, is partly offset by the regular incorporation of crop residues into the soil. Finally, ICLS, which include temporary pastures and sheep, demonstrate intermediate productivity levels compared to the other systems. However, they offer the greatest stability and resistance to extreme weather (+43% and +86% for stability compared to BAU and Vegan, in average), with better environmental performance. Therefore, our study reveals the benefits of crop‐livestock systems in terms of climate change adaptation, through stability and resistance to extreme climate events, and mitigation, through soil carbon sequestration and reduced greenhouse gas emissions and nitrate leaching. Moreover, our findings highlight the critical links between farm‐level circularity, soil‐crop feedbacks, human diet, and climate change.

Soil-crop feedbacks within contrasted cropping systems influence crop resistance to extreme climate events - Mathieu Delandmeter; Caroline De Clerck; Jérôme Bindelle; Benjamin Dumont (European Journal of Agronomy, 2026)

Integrated crop and livestock systems increase both climate change adaptation and mitigation capacities - Mathieu Delandmeter; Paulo César de Faccio Carvalho; Carolina Bremm; Carolina dos Santos Cargnelutti; Jérôme Bindelle; Benjamin Dumont (Science of The Total Environment, 2024)

A comprehensive analysis of CO2 exchanges in agro-ecosystems based on a generic soil-crop model-derived methodology - Mathieu Delandmeter; Joël Léonard; Fabien Ferchaud; Bernard Heinesch; Tanguy Manise; Ariane Faurès; Jérôme Bindelle; Benjamin Dumont (Agricultural and Forest Meteorology, 2023)